Evaluation of Teachers in Public schools in the Directorate of the University Brigade for the Experience of Distance Learning During the Corona Covid-19 Pandemic Compared to Face- to- Face Learning - Rayahneh, Mohammed Salman; Rashdan, Thani Ateeq; Al-Batayiha, Sawsen Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of distance learning in public schools in the University Brigade Directorate during the Corona Covid 19 pandemic. The average estimates of the teachers in the study sample of the reality of distance learning in government schools in the Second Amman Directorate got a total average of (2.45- 5), i.e. at a medium degree and at the level of the five domains; Communication got the highest overall average of (3.97), with a high grade, then teaching, with an average of (2.89) And thirdly, the difficulties with an average of (2.57) and both of them with a rating (average), the fourth for the content with an average of (1.74), and the fifth for the evaluation with an average of (1.54), both with a low rating, and there are no statistically significant differences at the level of significance (α≤0.05) between the sample answers due to the gender variable with the exception of the evaluation field and in favor of females. Based on these results, the researcher recommended teachers to change the assessment approach, modify the content and teaching methods to suit distance learning, and overcome technical and technological difficulties. He also suggested conducting other studies to identify the reality of distance learning in secondary and lower elementary schools.